Emx2 is an essential regulator of ciliated cell development across embryonic tissues - Thanh Khoa Nguyen; John-Michael Rodriguez; Hannah M. Wesselman; Rebecca A. Wingert (iScience)
Summary: Cilia are hair-like organelles with vital physiological roles, and ciliogenesis defects underlie a range of severe congenital malformations and human diseases. Here, we report that empty spiracles homeobox 2 (emx2) is essential for cilia development across multiple embryonic tissues including the ear, neuromasts and Kupffer’s vesicle (KV), which establishes left/right axial pattern. emx2 deficient embryos manifest altered fluid homeostasis and kidney defects including decreased multiciliated cells (MCCs), determining that emx2 is essential to properly establish several renal lineages. Further, emx2 deficiency disrupted renal monociliated cells, MCCs and led to aberrant basal body positioning. We reported that emx2 regulates prostaglandin biosynthesis in ciliogenesis and renal fate changes through key factors including ppargc1a, ptgs1 and PGE2. Our findings reveal essential roles of emx2 in tissue cilia development, and identify emx2 as a critical regulator of prostaglandin biosynthesis during renal development and ciliogenesis, providing insights relevant for future treatments of ciliopathies.